Pengaruh Strategi Promosi dan Harga terhadap Minat Beli Indihome di Wilayah Jakarta Utara - Ananda, Muhammad Rizki; Astono, Anjar Dwi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
The purpose of this study was to determine the promotion strategy and price on Indihome buying interest in the North Jakarta Region. This research uses validity test, reliability test, classical assumption test, normality test, multicollinearity test, and heteroscedasticity test, multiple linear regression, t test, F test, and coefficient of determination with the help of SPSS 23 program. The sample taken is 110 respondents. This study uses quantitative research methods, and with the aim of testing the hypotheses that have been set and can determine the effect of the independent variable on the dependent variable. The method that will be used by researchers for data collection is obtained by giving several questions to respondents through questionnaires. using a Likert scale to measure each statement. The results showed that the Promotion Strategy had no and significant effect on Buying Interest, Price had an effect on Buying Interest, and Promotion and Price Strategy had an effect on buying interest in the North Jakarta area.Keywords: Promotion Strategy, Price, Buying Interest.